Plasmatic carbonic anhydrase IX as a diagnostic marker for clear cell renal cell carcinoma. (1st January 2018) - Lucarini, Laura; Magnelli, Lucia; Schiavone, Nicola; Crisci, Alfonso; Innocenti, Alessio; Puccetti, Luca; Cianchi, Fabio; Peri, Sara; Supuran, Claudiu T.; Papucci, Laura; Masini, Emanuela
Abstract: Carbonic anhydrase (CA, EC 4.2.1.1) IX is regarded as a tumour hypoxia marker and CA inhibitors have been proposed as a new class of antitumor agents, with one such agent in Phase II clinical trials. The expression of some CAs, in particular the isoforms CA IX and CA XII, has been correlated with tumour aggressiveness and progression in several cancers. The aim of this study was to evaluate the possibility that CA IX could represent a marker related to clear cell Renal Cell Carcinoma (ccRCC). Bcl-2 and Bax, and the activity of caspase-3, evaluated in tissue biopsies from patients, were congruent with resistance to apoptosis in ccRCCs with respect to healthy controls, respectively. In the same samples, the CA IX and pro-angiogenic factor VEGF expressions revealed that both these hypoxia responsive proteins were strongly increased in ccRCC with respect to controls. CA IX plasma concentration and CA activity were assessed in healthy volunteers and patients with benign kidney tumours and ccRCCs. CA IX expression levels were found strongly increased only in plasma from ccRCC subjects, whereas, CA activity was found similarly increased both in plasma from ccRCC and benign tumour patients, compared to healthy volunteers. These results show that the plasmatic level of CA IX, but not the CA total activity, can be considered a diagnostic marker of ccRCCs. Furthermore, as many reports exist relating CA IX inhibition to a better outcome to anticancer therapy in ccRCC, plasma levels of CA IX could be also predictive for response to therapy.